2022
DOI: 10.1371/journal.pgph.0000163
|View full text |Cite
|
Sign up to set email alerts
|

The neglected epidemic—Risk factors associated with road traffic injuries in Mozambique: Results of the 2016 INCOMAS study

Abstract: In 2019, 93% of road traffic injury related mortality occurred in low- and middle-income countries, an estimated burden of 1.3 million deaths. This problem is growing; by 2030 road traffic injury will the seventh leading cause of death globally. This study both explores factors associated with RTIs in the central region of Mozambique, as well as pinpoints geographical “hotspots” of RTI incidence. A cross-sectional, population-level survey was carried out in two provinces (Sofala and Manica) of central Mozambiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent case studies provided some empirical evidence using various models. Peralta-Sanotos et al (2022) analysed risk factors associated with road traffic injuries in Mozambique, focusing on urbanicity, ownership of a car or motorcycle and socioeconomic strata index in their analysis [14]. The study found a 47% decrease, 92% increase and 26% decrease in the rate of RTI for urban residence, motorbike ownership and high socioeconomic status, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent case studies provided some empirical evidence using various models. Peralta-Sanotos et al (2022) analysed risk factors associated with road traffic injuries in Mozambique, focusing on urbanicity, ownership of a car or motorcycle and socioeconomic strata index in their analysis [14]. The study found a 47% decrease, 92% increase and 26% decrease in the rate of RTI for urban residence, motorbike ownership and high socioeconomic status, respectively.…”
Section: Introductionmentioning
confidence: 99%